2015
DOI: 10.1007/s10549-015-3401-8
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index associated with genome-wide methylation in breast tissue

Abstract: Gene expression studies indicate that body mass index (BMI) is associated with molecular pathways involved in inflammation, insulin-like growth factor activation, and other carcinogenic processes in breast tissue. The goal of this study was to determine whether BMI is associated with gene methylation in breast tissue and to identify pathways that are commonly methylated in association with high BMI. Epigenome-wide methylation profiles were determined using the Illumina HumanMethylation450 BeadChip array in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 46 publications
(65 reference statements)
0
31
0
Order By: Relevance
“…Selection criteria for the Normal Breast Study included having an invasive ductal carcinoma with a tissue specimen sampled ≥4 cm from tumor margins, undergoing reduction mammoplasty, or undergoing prophylactic surgery (21). There were 150 participants with invasive breast cancer had tissue collected that was >4 cm from the tumor.…”
Section: Methodsmentioning
confidence: 99%
“…Selection criteria for the Normal Breast Study included having an invasive ductal carcinoma with a tissue specimen sampled ≥4 cm from tumor margins, undergoing reduction mammoplasty, or undergoing prophylactic surgery (21). There were 150 participants with invasive breast cancer had tissue collected that was >4 cm from the tumor.…”
Section: Methodsmentioning
confidence: 99%
“…Normal breast tissue samples used in this study come from women enrolled in the NBS [40]. NBS contacted 526 women above 18 y of age who were undergoing breast surgery at the University of North Carolina Hospitals.…”
Section: Study Populationmentioning
confidence: 99%
“…Three studies had mixed breast cancer patients and breast cancer-free Discovery sample column: *n not obese/n obese; # Data from meta-analysis are combined; ˚Mean between women's data and men's data; NW stands for normal weight, OW for overweight, OB for obese and V for visit. LDA column: 1 Leukocyte distribution adjustment; 2 The influence of leukocyte composition was adjusted using the algorithm described by Houseman et al (80); 3 The influence of leukocyte composition was adjusted by subtype cell count; 4 The influence of leukocyte composition was adjusted using SVA function; 5 CD4 + T-cell purity was estimated using the methods described participants: one was a meta-analysis of four studies (EPIC-Italy, EnviroGenoMarkers, NOWAC, EPIC-Netherlands) that included both men and women (43), another was derived from the Sister Study cohort which included only healthy women at enrollment with a sister with breast cancer (44), and finally, one that included only women (45). Our study included only female patients with breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of included participants varied. Two studies reported mean age under 30 years (24,32), eight included participants with a mean age of 30-50 years (25,29,30,33,34,36,37,39), nine others included participants with a mean age of 50-60 years [ (13,27,35,38,41,(43)(44)(45) and the present study], and the last five had participants with a mean age above 60 years (26,28,31,40,42). The forty study participants from our study ranged in age from 33 to 69 years, with a mean age of 51.0 (standard deviation [SD] ±8.2) years.…”
Section: Description Of Studies Characteristics Of Included Studies mentioning
confidence: 99%
See 1 more Smart Citation